Social representations, imaginaries and territorialities constructed by communities near hydroelectric megaprojects in Bolivia - Kunstek-Salinas, Luis-Camilo (2024)
Introduction: For an evaluation of the impacts generated by development projects in rural communities in Bolivia, it is of utmost importance to incorporate the social dimension from a qualitative and participatory approach to capture territorial dynamics and the reconstruction of the historical memory of the communities and their relationship with development projects. Objective: To determine the social representations, imaginaries and territorialities constructed by the communities close to the hydroelectric megaprojects, in relation to the presence of development projects and their relationship with family and community life projects. Methodology: This research has been carried out using a transdisciplinary approach, based on qualitative approaches, prioritising dialogue with the communities. Documentary, newspaper and periodical sources have been reviewed, in addition to the implementation of communal workshops, group interviews, individual interviews and talking maps. Conclusions: An evaluation that seeks to reflect the impact of development projects on surrounding communities must have a participatory approach. It should incorporate a qualitative approach that captures subjective and narrative aspects.  Traditional indicators need to be broadened to include social dimensions such as language, creativity, collective memory and community relations.